Entre prouesse et dérision - Victor A. Stoichita (Ateliers d'Anthropologie)
This article focuses on a type of virtuosity which involves the imitation of non-musical sounds in the context of musical performances. It attempts to describe the modalities of these moments of acrobatics in bluegrass and country music in North America. To highlight the historical evolution of this virtuosity system, the analysis follows the transformation of a particular melody, known as the Orange Blossom Special, which remains to this day one of the most famous imitations of trains in North American music.